1996
DOI: 10.1093/oxfordjournals.humrep.a019148
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryology: Undocumented embryos: do not trash them, FISH them

Abstract: Pronuclei formation is routinely assessed 16-20 h after oocyte insemination in in-vitro fertilization (IVF). Occasionally, the pronuclei disappear before this time, rendering them as 'undocumented'. Since the number of pronuclei detected is used to distinguish normal from abnormal embryos in the context of ploidy, the diploidy of undocumented embryos is questionable, and therefore they are routinely discarded. The introduction of fluorescent in-situ hybridization (FISH) technology allows the assessment of ploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 8 publications
3
44
0
Order By: Relevance
“…In this study, 11.3 % 0PN-derived embryos were observed with an average age of 32.8 comparable with our general patient population, suggesting that aging is not a significant contributory factor to the occurrence of 0PN-derived embryos. This finding is consistent with previous reports [6].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In this study, 11.3 % 0PN-derived embryos were observed with an average age of 32.8 comparable with our general patient population, suggesting that aging is not a significant contributory factor to the occurrence of 0PN-derived embryos. This finding is consistent with previous reports [6].…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that the percentage of embryos from 0PN oocytes may vary from 12.7 to 20 % of day 3 embryos [6]. In this study, 11.3 % 0PN-derived embryos were observed with an average age of 32.8 comparable with our general patient population, suggesting that aging is not a significant contributory factor to the occurrence of 0PN-derived embryos.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations